KUMBANG PENGGEREK PADA BEBERAPA JENIS KAYU LEGUMINOSAE - WORO A. NOERDJITO; M. AMIR (Research Center for Biology-Indonesian Institute of Sciences, 1986)
W A. NOERDJITO&M.AMIR.1986.wood boring beetle of some leguminosae timbers.Berita Biologi 3(4): 159-162.At least 8 families of wood boring beetles were observed to cuse a damage on some leguminous timbers belong to the genus of Bauhinia,Albizia , Acacia,Sesbania,Erythrina and Glericida.They were namely Scolytidae(5Species),Platypodidae(4 species),Boctrychidae(6 species),Elateridae(1 species),Tenebrionidae(4 species),Erotylidae(1 species),Lucanidae(1 species) and Cetonidae(1 species).Hostplant selection of the beetles seemed to be determined by the timber species,as well as their state of decompositions.